The Role of Internationalization Orientation in Mediating the Relationship between Capabilities and Intention to Export: An Empirical Analysis on SMEs - Yusuf Wibisono, Yogi; Sitorus, Hotna Marina (International Journal of Industrial Management, 2021)
Small and Medium Enterprises (SMEs) have a strategic role in the Indonesia’s economy; however, they have a low contribution on the national export. Studying on SMEs internationalization becomes important to understand factors that influence them to go international. Using resource-based view perspective, the objective of study is to investigate how the organizational capabilities influence the intention of SMEs to export through internationalization orientation. A model was developed that explained the impact of personnel management, product development, and production capabilities on internationalization orientation, and eventually affect the export intention. Primary data were collected through a field survey by distributing structured questionnaires to SMEs over three months, resulting 86 eligible responses. These empirical data were analyzed to validate proposed model using partial least square - structural equation modeling technique (PLS-SEM). The results indicated that internationalization orientation mediated partially the effect of personnel management and product development capabilities on SMEs intention to export. The other finding displayed the unexpected result that there was insignificant influence of production capabilities on internationalization orientation and export intention. This study suggests that to increase the intention of SEMs to export, the firms must have capabilities in managing their personnel and developing unique and innovative product consistently.